Multiscale structural analysis of polymorphic phase boundaries in doped antiferroelectric sodium niobate - Kumar H.; Ghose S.; Erasmus R.; Tripathi S. (My University, 2025)
In the current work, we have performed multiscale structural analysis of a Pb-free sodium niobate-based smart system, i.e., 0.9NaNbO3-0.1Ba0.9Ca0.1TiO3 (NN-10BCT) reported earlier for its high ferroelectric response. We have investigated the temperature-dependent evolution of crystal structure at long, medium, and short ranges using synchrotron x-ray diffraction (SXRD), Raman scattering, and pair distribution function(PDF) techniques in conjunction with dielectric studies. Temperature-dependent synchrotron x-ray diffraction data combined with dielectric analysis suggest two unique polymorphic phase boundaries (PPB) with two coexisting ferroelectric phases stable in the wide temperature ranges. These PPBs are stable in different regions viz. (i) cryogenic temperatures with coexisting R3c and Pmc21 phases (ii) vicinity of room temperatures with coexisting Pmc21 and Amm2 phases. In contrast to the conclusions drawn from SXRD, PDF reveals structures having lower symmetry (with coexisting Cc+ Pmc21 phases at 1.7 ≤r≤ 20 Å) at short ranges for these PPBs. The presence of different long- and short-range symmetries (accommodating tilt-oriented ferroelectric phases) in the unique polymorphic phase boundaries makes them thermally stable and advantageous for technological applications. © 2025 American Physical Society.